DETERMINAN PENDAPATAN NELAYAN DI PULAU AMBON - Stellamaris Metekohy (Jurnal Cita Ekonomika, 2020)
Ambon Island has potential fishery resources to be developed in the future because the fishing community on the coast is used as a source of income and the level of income depends on the catch. This study aims to determine the level of income of fishermen on the coast and the factors that influence it, including: capital factors, experience at sea, education level proxied by dummy variables and length of time at sea. The results obtained are that the factors of capital, fishing experience and education level have a positive and significant effect on fishermen's income, while the length of time at sea has no significant effect on fishermen's income. The analytical tool used is multiple regression analysis.